Condition of nasopharynx contamination in children with chronic tonsillitis and gastroesophageal reflux disease - L. M. Boiarska; L. V. Hrebeniuk; K. O. Ivanova; V.V. Akhtyrsky (Zaporožskij Medicinskij Žurnal)
The aim was to study the condition of nasopharynx contamination in children with chronic tonsillitis depending on the presence of pathological gastro-esophageal reflux.